MORPHOLOGICAL ANALYSIS OF BATHYMETRIC AND MAGNETIC ANOMALY DATA FOR GEOSPATIAL CHARACTERIZATION OF THE NIEUWERKERK SEAMOUNT - Eva Mukaromah, Karin
Eastern Indonesia region is tectonically complicated and composed of several oceanic and continental fragments that become complex deformation zones, forming various underwater features. In particular, seamounts are spectacular bathymetry features, commonly forming within a volcanic and tectonically active continental margin. This study focuses on characterizing the Nieuwerkerk Seamount in Banda Sea by analysis its morphology, morphometry, and physical characteristics. A geophysical survey covering bathymetry and magnetic mapping was carried out through the Jalacitra II-2022 “Banda” Expedition initiated by the Indonesian Navy’s Hydro-Oceanographic Centre (Pushidrosal) in Banda Sea to identify the physical characteristic of the Nieuwerkerk. Bathymetry data was acquired using the Kongsberg 30 kHz EM302 multibeam echosounder (MBES), while magnetic data was acquired using the Geometrics G-882 magnetometer. Multibeam bathymetry is processed by extracting elevation, contour, slope, aspect, flow direction information to identify the morphology and morphometry of the seamount. Then the magnetic anomaly data will complement the early physical characterization of the seamount by analyzing the analytic signal of the magnetic anomaly. The result of this study shows that there are several zones of landslides potential in the seamount by analyzing its geomorphometric structures. The zones of landslide potential are defined by analyzing the slope and aspect of the area. From the magnetic data is known there are potential sources of volcanic rocks, especially on the summit plateau area. The obtained data can be used to describe the geomorphometric structures and the potential sources of volcanic rocks, but without any seafloor sample the activity of the seamount cannot be defined its active or not.